2016
DOI: 10.1080/03906701.2016.1259125
|View full text |Cite
|
Sign up to set email alerts
|

Assessing income support where no national minimum income scheme exists. Is it possible to apply the model family method to the Italian case?

Abstract: This article focuses on the application of a specific comparative\ud methodology, the model family method (MFM), in measuring the\ud income derived from minimum income schemes. The application\ud of the MFM to the analysis of this policy field shows several\ud criticalities such as the difficulty to analyze countries in which no\ud national scheme exists, and in which both the intra-national\ud variations and the discretionary power of street-level bureaucrats\ud are significant. Stemming from the application … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Efficient management of net national income not only helps to sustain and increase economic growth but also benefits the livelihoods of people. Arlotti and Sabatinelli (2017) explored the support of net national income with the minimum income schemes for workers that influence income inequality. The results revealed that net national income is a strong factor related to global income that significantly impacts income inequality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Efficient management of net national income not only helps to sustain and increase economic growth but also benefits the livelihoods of people. Arlotti and Sabatinelli (2017) explored the support of net national income with the minimum income schemes for workers that influence income inequality. The results revealed that net national income is a strong factor related to global income that significantly impacts income inequality.…”
Section: Literature Reviewmentioning
confidence: 99%